Use of an electronic consultation system in an inner city general practice: a mixed-methods service evaluation - Katherine Leung (BMJ Open Quality)
Background The COVID-19 pandemic propelled the uptake of electronic consultation (e-consultation) tools. Such tools promise to increase access and improve efficiency. Previous research has highlighted unintended consequences associated with e-consultation use.Aim To explore patient and staff views, experiences and usage of an e-consultation tool in a general practice setting, 2 years after the start of the COVID-19 pandemic.Design and setting A mixed-methods service evaluation of an e-consultation tool (eConsult) in an inner city general practice.Methods E-consultations submitted between June and August 2022 (n=972) and associated electronic medical records were quantitatively analysed for the reason for query, type of response and whether it was followed by a reconsultation within 14 days. Reflexive thematic analysis on qualitative interviews with patients and staff (n=18).Results 76% of e-consultations were followed by a face-to-face or telephone encounter as the primary response type. 21% of e-consultations were followed by a reconsultation for the same problem within 14 days.E-consultations brought advantages for some patients in terms of access and convenience; however, other patients described a negative impact on expression, recognition of symptoms and the patient–doctor relationship. The access provided by eConsult surpassed practice capacity, leading to reports of clinician burnout. There was an incongruous view on the purpose of e-consultations among patients and staff.Conclusion Evaluation of e-consultation tools is essential to ensure staff and patient needs are met. Although some benefits of e-consultations were identified, a number of unintended consequences were reported, including negative impacts on workload, patient communication and the patient–doctor relationship.